2013
DOI: 10.4103/0971-5851.123723
|View full text |Cite
|
Sign up to set email alerts
|

Report of chronic myeloid leukemia SMS Medical College Hospital, Jaipur

Abstract: This is a retrospective analysis of patients of chronic myeloid leukemia (CML) registered and under treatment at the Leukemia Lymphoma Clinic at the Birla Cancer Center, SMS Medical College Hospital, Jaipur. Approximately, two-thirds of the patients are getting imatinib mesylate (IM) through the Glivec International Patient Assistance Program while the rest are on generic IM. In addition to comparison of hematological and molecular responses in the Glivec versus the genetic group, in this analysis, an attempt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…It is noteworthy that patients in lower socioeconomic (SE) class presented with higher Sokal scores and with more disease burden as described from SMS Medical College Hospital, Jaipur, indicating probably a late diagnosis. [25] Interestingly, the data from TMH, Mumbai, Maharashtra, India, showed that irrespective of the Sokal score, the CCyR was similar, i.e., for low risk (76.3%), intermediate risk (73.8%), and high risk (77.3%), suggesting that IM may overcome this aspect of disease. [15] Studies from TMH and SMS, Jaipur, also compared the responses of innovator Glivec to the Indian IM and found similar hematological responses, cytogenetic and better molecular responses with generic.…”
Section: Treatment and Monitoringmentioning
confidence: 97%
See 2 more Smart Citations
“…It is noteworthy that patients in lower socioeconomic (SE) class presented with higher Sokal scores and with more disease burden as described from SMS Medical College Hospital, Jaipur, indicating probably a late diagnosis. [25] Interestingly, the data from TMH, Mumbai, Maharashtra, India, showed that irrespective of the Sokal score, the CCyR was similar, i.e., for low risk (76.3%), intermediate risk (73.8%), and high risk (77.3%), suggesting that IM may overcome this aspect of disease. [15] Studies from TMH and SMS, Jaipur, also compared the responses of innovator Glivec to the Indian IM and found similar hematological responses, cytogenetic and better molecular responses with generic.…”
Section: Treatment and Monitoringmentioning
confidence: 97%
“…[15] Studies from TMH and SMS, Jaipur, also compared the responses of innovator Glivec to the Indian IM and found similar hematological responses, cytogenetic and better molecular responses with generic. [15,25] Unfortunately, a significant number of patients in the Glivec arm were not tested for molecular responses for economic reasons making the difference artifactual.…”
Section: Treatment and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be noted that cytogenetic and molecular responses were better in the group of patients treated with generic imatinib. These results could be explained by the fact that molecular responses were not documented in 42% of patients in the Glivec arm because of economic reasons 16 .…”
Section: Discussionmentioning
confidence: 99%
“…MMR rate was quite similar between these two groups 15 . The other study from India included 213 patients of CML [16]. 64% of patients were on GIPPAR Glivec, while 36% are on generic imatinib.…”
Section: Discussionmentioning
confidence: 99%